A deal between the river and me: the experience of the Student Community Service in the Liceo de Moravia, Costa Rica (Biocenosis, 2012)
Environmental Education can be present in the Student Community Service activities as a way that allows students to know and identify better with the living environment and promote the development of capabilities that prompts them to engage in actions to conserve environment. This experience was developed between March and July 2011, with the participation of 37 students in the tenth grade of Liceo de Moravia, who analyzed the environmental situation in the upper basin of the Rio Virilla with water samples taken in three streams for determine the Biological Monitoring Working Party adapted to Costa Rica (BMWP-CR). Assessment identified in the participants, the development of new skills to talk in public, defend their ideals, analyze environmental problems and possible solutions.
Keywords: Monitoring; La Motte Kit; Macroinvertebrates; Biological Monitoring Working Party adapted to Costa Rica; Reforestation